Binary Opposition in Narrations of “Native” in Social Media - Puspitasari Puspitasari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2018)
The “native” or pribumi term as a narrative emerged into the public sphere and raises questions since October 16, 2017, whether the term is merely a conversation on the surface or more deeply describes the narrative that represents the socio-cultural aspect of Indonesian society. The study was conducted using twitter as a locus of observation within the period of November 8-16, 2017. Based on the idea that a social text reflects a narrative building constructed socio-cultural and leaves a long history trail, preliminary findings indicate that Indonesian society has a historical heritage of Dutch colonialism on native and non-native (Chinese/Tionghoa). The "native" narratives of the present are not only built on the issue of social inequalities between native versus Chinese, but rather show imaginations about the influence of the Chinese group's economic resources on power. The narrative does not only touch on the economic and political aspects, but also the religions, historically potentially becoming a conflict played by interest groups ahead of the 2018 elections and the 2019 presidential election. Suggestions for anticipating vulnerabilities are to conduct media literacy programs involving multiple stakeholders, both government and civil society, include scholars.